Mindfulness-Based Practices for Multicultural Meditation Practitioners to Develop Mental Well-Being - Jiwattanasuk, Narumon; Vasuratna, Voranij; Deegalle, Mahinda (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
This research investigates mindfulness-based practices for enhancing the mental well-being of multicultural meditation practitioners. The study is conducted in three phases with the following objectives: 1) To study the mental well-being circumstances and analyze the problems of multicultural meditation practitioners, 2) To develop the process of mindfulness-based practice for the mental well-being of multicultural meditation practitioners, and 3) To evaluate the process of mindfulness-based practice for the mental well-being of multicultural meditation practitioners. A mixed-methods approach was employed, combining qualitative research with quantitative pre- and post-test assessments and in-depth interviews. The research was conducted at Wat Thai Buddharam in Brisbane, Australia. The study involved 30 participants who were selected through purposive sampling. These individuals represent a wide range of cultural backgrounds, including various religions, languages, and ethnicities. The findings reveal that multicultural meditation practitioners face various psychological challenges, including stress, anger, and mental distress, despite their good health and financial security. The study developed a culturally sensitive mindfulness-based intervention, resulting in the "Mindfulness Wisdom and Loving-kindness" (MWL) program. This program, designed to enhance mental health and inner peace in multicultural settings, emphasizes inclusivity and diverse activities. The evaluation, using questionnaires and interviews, demonstrated significant improvements in participants’ mental health, confirming the benefits of mindfulness practices tailored to diverse cultural backgrounds.